Milk & Bread - Susan Goldberg (Canadian Food Studies)
The found-object collage series Milk & Bread was inspired in large part by the impact of the COVID-19 pandemic on women and mothers in particular, who bore the brunt of increased domestic duties and childcare during lockdowns and school closures, and who left the workforce in far greater numbers than fathers. The relentless domesticity and unchanging nature of family life under lockdown is mirrored in the repetitive, sometimes obsessive, arrangement of the tags, identical, with only minor variations to mark the time. Milk & Bread was created with milk and bread tags donated by individual households, daycare centres, and community organizations with the mission of providing food to vulnerable populations.